KAPABILITAS DINAMIS DALAM MEMEDIASI PENGARUH KESIAPAN UNTUK BERUBAH DAN KEPEMIMPINAN YANG LINCAH TERHADAP EKOSISTEM DIGITAL UKM - Rozak, Hasan Abdul; Basiya, R; Fitriati, Ika Rosyada (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2022)
This study aims to describe and analyze the effect of readiness for change and agile leadership on the dynamic capabilities of SMEs. Furthermore, this study also examines the influence of dynamic capabilities on strengthening the digital ecosystem of SMEs. If SMEs are ready to change and have agile leadership, it will increase their dynamic capabilities. This dynamic capability of SMEs will ultimately improve the lives and long-term sustainability of SMEs in the digital world. This type of research is explanatory research to analyze SMEs’ digital ecosystem improvement. This research uses regression analysis methods and path analysis in managing data. The sampling technique used non-random sampling with a purposive sampling method. Data were collected from 250 SMEs in Central Java through a questionnaire. The results of the study show that readiness for change and agile leadership can increase the dynamic capabilities of SMEs. The increasing dynamic capabilities of SMEs are proven to be able to strengthen the digital ecosystem for SMEs. The results of this study are expected to contribute to SMEs strengthening the growth of the digital economy in Indonesia. The urgency of this research relates to factors that can strengthen the SME digital ecosystem and contribute to improving the economy.